Finite and algorithmic model theory - Esparza, Javier; Michaux, Christian; Steinhorn, Charles (Cambridge New York Cambridge University Press, 2011)
"Intended for researchers and graduate students in theoretical computer science and mathematical logic, this volume contains accessible surveys by leading researchers from areas of current work in logical aspects of computer science, where both finite and infinite model-theoretic methods play an important role. Notably, the articles in this collection emphasize points of contact and connections between finite and infinite model theory in computer science that may suggest new directions for interaction. Among the topics discussed are: algorithmic model theory, descriptive complexity theory, finite model theory, finite variable logic, model checking, model theory for restricted classes of finite structures, and spatial databases. The chapters all include extensive bibliographies facilitating deeper exploration of the literature and further research"--Provided by publisher.
Preface / Javier Esparza, Christian Michaux and Charles Steinhorn -- Automata-based presentations of infinite structures / Vince Bárány, Erich Grädel and Sasha Rubin -- Logical aspects of spatial databases / Bart Kuijpers and Jan Van den Bussche -- Some connections between finite and infinite model theory / Vera Koponen -- Definability in classes of finite structures / Dugald Macpherson and Charles Steinhorn -- Algorithmic meta-theorems / Stephan Kreutzer -- Model theoretic methods for fragments of FO and special classes of (finite) structures / Martin Otto.
Includes bibliographical references and index.
Includes bibliographical references.
Keywords: Finite model theory; Computer science -- Mathematics